ESTABLISHING THE CONTENT OF AN EMPLOYEE’S LABOR FUNCTION AS A MANDATORY CONDITION OF THE EMPLOYMENT AGREEMENT - Дігтяренко, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to explore the specifics of establishing the content of an employee’s labor function as a mandatory condition of the employment agreement. Research methods: comparative analysis, objective truth, cognitive-analytical, structural, etc. Results: the content of an employee’s labor function and the procedure for establishment are generalized. Discussion: problems of fixing of the labor responsibilities that make up the content of an employee’s labor function, their changes and ways to improve the legal regulation of the labor function as a mandatory condition of the employment agreement. Establishing the content of an employee’s labor function is extremely important not only for the institute of the employment agreement, but also for the field of labor law in general. In connection with numerous violations of employees’ rights in practice, the issue of how an employee’s labor function is related to the range of duties performed by an employee needs. The analysis of the case law shows that the courts have a fairly subjective understanding of the concept of «labor function». At the same time, the constant improvement of the means of production and the related new approaches of the employer to the organization of labor exclude the possibility of maximizing the specification of the range of labor duties of the employee. Thus, the question of the content of an employee’s labor function remains one of the most debatable and complex in the science of labor law. Based on the analysis of legislation, case law and doctrinal developments, we conclude that a profession, position, specialty and qualification are structural elements of an employee’s labor function. The content of the labor function, that is, the specific type of work and the range of labor responsibilities of the employee is established on the basis of these structural elements of the labor function and within them. At the same time, establishing the content of an employee’s labor function is the exclusive competence of the parties to the employment agreement. The job instructions can be amended, supplemented only on the order of the head of the enterprise, institution, organization with the consent of the employee. An order for changes and additions to the job instruction is issued in the case of redeployment of duties between employees due to reduction in numbers, rational division of labor. The content and range of labor responsibilities may vary depending on the conditions of labor organization, but within the specified an employee’s labor function. After all, in Section «Tasks and Responsibilities» of Issue 1, «Professions of employees common to all economic activities» of the Directory of qualification characteristics of the professions of employees’ occupations sets out typical professional tasks, duties and responsibilities for a particular position.